PERAN GURU DALAM MENGEMBANGKAN KARAKTER RELIGIUS SISWA DI KELAS V SD SWASTA BAKTI LUHUR KECAMATAN MEDAN HELVETIA - Nur Hayati Putri; Hendri Irawan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
The purpose of this study is the teacher’s role in developing the religious character of students at school class V SD Private Bakti Luhur, Medan Helvetia sub-district.This type of research is descriptive research that is describing and interpreting the data that has been obtained by using the observation method, interview method and documentation method. The problem in the research is about how the teacher’s role in developing the religious character of student’s is all discussed and revealed in guiding the religious character of students as an effort to form student’s personalities in worship, both worship activities at school and in the family environment (home).The result obtained in this study are the teacher’s role in developing the religious character of student’s by taling a more intense approach to them by inviting them to talk motivating, suggesting them about the importance of learning, opening their awareness with religious teaching encourage studying hard and expecting reward from God Almighty. And also shows that the role of religious teachers as role models and partners of students in learning has been carried out well as the professionalism of teachers in teaching and handling and dealing with various kinds of student characters. And it is done for the purpose of smoothness in the learning process and to improve student learning outcomes.